Towards Harmony and Balance: A Policy Framework for State Islamic Higher Education Leaders in Nurturing Student Religious Moderation - Hambali, Muh; Muttaqin, Imamul; Mubarak, Ruma (JURNAL AL-TANZIM, 2023)
This study aims to analyze university policies in encouraging religious and multicultural moderation. The method used is a qualitative case study type method. Data collection techniques were carried out through interviews, observation, and documentation. The data analysis technique consists of three lines of activity that co-occur: data reduction, data presentation, and conclusion. The results of this study indicate that the characteristics of fostering religious moderation using the General Lecture Material (MKU) approach are Citizenship Education and University Specificity Courses (MKKU), which are called Ulul Albab Courses. MKU through the insertion of multicultural values in lectures and seminars within the university and faculties. At the same time, MKKU uses an approach to determining courses as institutional-specific courses. The dissemination of moderate Islamic values impacts student behavior which can build social relations and openness in the academic environmental ecosystem. This strengthens students' thinking patterns from closed to open thinking. Extreme thoughts and behaviors can be avoided in higher education tri-dharma activities.